Kompetensi Profesional Guru Sebagai Upaya dalam Meningkatkan Kinerja Guru di SMP Negeri 1 Muara Padang: Penelitian - Amalia Sriwijayani; Nur Ahyani; Nila Kesumawati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to determine and describe the professional competence of teachers as an effort to improve teacher performance at SMP Negeri 1 Muara Padang and the efforts made by the principal in developing professional competence of teachers in improving teacher performance at SMP Negeri 1 Muara Padang. The method used is a qualitative method. Data collection techniques using observation, interviews and documentation. The results of the study can be concluded that the Professional Competence of Teachers as an Effort to Improve Teacher Performance at SMP Negeri 1 Muara Padang, is very good, from the results of the author's research that some teachers have been able to foster student interest in learning. professional competence, and the Principal's efforts in Improving Professional Competence of Teachers at SMP Negeri 1 Muara Padang include attending Training, and attending KKG, conducting Classroom Action Research (PTK), and actively participating in professional organizations. And provide coaching to teachers, provide supervision, hold training, conduct visits between schools, and provide opportunities for teachers to continue their education.